Knowledge Management Practices and Absorptive Capacity Applied to Performance and Quality Improvement in Industrial Maintenance (Research, Society and Development, 2021)
This research aims to identify and describe how knowledge management practices and absorptive capacity have been used to improve performance and quality in the maintenance area of an automobile industry in the State of São Paulo (Brazil). In order to achieve this goal, a qualitative descriptive research was carried out using the case study method. There were applied as investigation instruments semi-structured interview, direct non-participatory observation and documentary research in records of files and physical artifacts of the analyzed company. Managers and technical employees of high hierarchy of the industrial maintenance area of the prospected company were interviewed. It was identified that the professionals in the maintenance area perceive the need for knowledge management in their work processes and that knowledge management practices have an influence on the absorptive capacity of the area. It was also achieved that the absorptive capacity influences the performance and quality of the actions performed by the maintenance employees. In conclusion, the results of the research allow us to infer that if organizations pay greater attention to knowledge management practices and the absorptive capacity they provide, they can create and sustain competitive advantages over their competitors.